A new model for the influence of particle arrangement and interphase on the stiffness of particulate composites. Issue 4 (21st March 2017) - Sideridis, E.
ABSTRACT: In this work, the stiffness of a composite containing spherical particles surrounded by an inhomogeneous interphase embedded in an isotropic matrix is evaluated. The elastic constants of the interphase are modeled as continuous radial functions. It is assumed that this third phase developed between the polymeric matrix and the filler particles contains both areas of absorption interaction in polymer surface layers onto filler particles and areas of mechanical imperfections.It can be said that the concept of boundary interphase is a useful tool to describe quantitatively the adhesion quality between matrix and particles and that there is an effect of this phase on the thermomechanical properties of the composite. The thickness and volume fraction of this phase were determined from heat capacity measurements for various filler contents.On the other hand, it is assumed that the particle arrangement (distribution) and their interactions should affect the thermomechanical constants of the composite.The theoretical predictions were compared with experimental results as well as with other theoretical values derived from expressions given in the literature and in some cases, they were found to be in a reasonable agreement.